2016
DOI: 10.4049/jimmunol.1501206
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Controls Effector T Cell Differentiation through β2-Adrenergic Receptor–Mediated Inhibition of NF-κB and AP-1 in Dendritic Cells

Abstract: Despite accumulating evidence indicating that neurotransmitters released by the sympathetic nervous system can modulate the activity of innate immune cells, we still know very little about how norepinephrine impacts signaling pathways in dendritic cells (DC) and the consequence of that in DC-driven T cell differentiation. In this article, we demonstrate that β2-adrenergic receptor (β2AR) activation in LPS-stimulated DC does not impair their ability to promote T cell proliferation; however, it diminishes IL-12p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 36 publications
2
57
1
2
Order By: Relevance
“…Tumor immunosuppressive microenvironment inhibits dendritic cell functions [64, 65]. Especially, norepinephrine released in the microenvironment alters antigen presentation by dendritic cells, which reduces cytotoxic T-cell priming [66, 67]. Here we observed that propranolol decreases the number of dendritic cells in the primary tumor and improves CD8 + T-cell activity.…”
Section: Discussionmentioning
confidence: 59%
“…Tumor immunosuppressive microenvironment inhibits dendritic cell functions [64, 65]. Especially, norepinephrine released in the microenvironment alters antigen presentation by dendritic cells, which reduces cytotoxic T-cell priming [66, 67]. Here we observed that propranolol decreases the number of dendritic cells in the primary tumor and improves CD8 + T-cell activity.…”
Section: Discussionmentioning
confidence: 59%
“…β 2 ARs are the most expressed AR on immune cells and considered the main mediators of CA immune effects; their activation usually results in anti-inflammatory effects 6 , 20 , 21 . Indeed, stimulation of β 2 AR modulates cytokine production by activated innate immune cells, primarily inhibiting proinflammatory cytokines, such as TNF-α, IL-12 and IL-6, and by increasing IL-10 and IL-33 release by these cells 22 - 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the dendritic cells, it is well-known that these specialized phagocytes are responsible for bridging innate and adaptive immune responses [49], and that β-stimulation turns DCs to an anti-inflammatory state [50] and triggers T cell differentiation [51]. Indeed, sympathetic stimulation is essential for triggering the recovery phase of an immune response [52,53] in lymph nodes [54], bone marrow cells [55], and gut macrophages [56].…”
Section: Discussionmentioning
confidence: 99%